2006
DOI: 10.1007/s00414-006-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Carisoprodol intoxications: a retrospective study of forensic autopsy material from 1992–2003

Abstract: Carisoprodol is commonly prescribed as a centrally acting muscle relaxant, but it is also subject to abuse. The literature describing fatal intoxications with the drug is limited to a relatively small number of cases, and there are inconsistencies with regard to which concentration levels that are toxic. We therefore investigated all forensic autopsies at the Norwegian Institute of Public Health during the period 1992-2003 where carisoprodol was detected. The median concentrations of carisoprodol in intoxicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
5
15
0
Order By: Relevance
“…The figures above were supported by two Norwegian studies (60,61). In these studies, there was a close temporal relationship between the amount of carisoprodol sold in Norway and both the number of contacts made to the Poisons Information Centre and the number of forensic autopsies where carisoprodol was found.…”
Section: Intoxicationssupporting
confidence: 60%
See 1 more Smart Citation
“…The figures above were supported by two Norwegian studies (60,61). In these studies, there was a close temporal relationship between the amount of carisoprodol sold in Norway and both the number of contacts made to the Poisons Information Centre and the number of forensic autopsies where carisoprodol was found.…”
Section: Intoxicationssupporting
confidence: 60%
“…On the basis of these publications and later studies which substantiated the abuse potential of the drug (72), the increased traffic accident risk (40) and the intoxication dangers (60,61), the Norwegian Medicines Agency again started a review of the benefit risk ratio of carisoprodol. This concluded that the risk benefit balance was negative.…”
Section: The Regulatory Fate Of Carisoprodolmentioning
confidence: 99%
“…This is a situation unlike the one for carisoprodol, where the correlation between sales numbers and findings in drugged drivers was very high; this indicates that most drug use came from legal sources. This drug was removed from the Norwegian market due to its potential for misuse and toxic effects [18,19]. Moreover, an Australian study found that alprazolam findings in drug-related deaths were more related to prescribed alprazolam than clonazepam in our study [20].…”
Section: Discussionmentioning
confidence: 91%
“…Recently, alprazolam and carisoprodol have been noted to cause significant harm to patients in overdoses. 35,36 Alprazolam was specifically associated with an increased ICU length of stay when compared to other benzodiazepines. Flumazenil as a diagnostic agent in benzodiazepine overdose should be used cautiously, especially in those patients with chronic benzodiazepine use, epilepsy, or coingestion with medications that may increase the risk for seizures such as tricyclic antidepressants.…”
Section: Analgesicsmentioning
confidence: 97%